2016
DOI: 10.1007/s10342-016-1009-0
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of Asian, European and North American Fraxinus species to the ash dieback pathogen Hymenoscyphus fraxineus reflects their phylogenetic history

Abstract: In Europe, common ash (Fraxinus excelsior) is being decimated because of the invasive fungus Hymenoscyphus fraxineus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 68 publications
(86 reference statements)
6
79
1
Order By: Relevance
“…fraxineus , local ash species are resistant to the fungus although it is a foliar pathogen (Cleary et al , ; Drenkhan et al , ). Nielsen et al () further showed that the pathogen could grow and reproduce on leaf rachises of different ash species that were not affected by ash dieback. Based on the accumulating knowledge on the ecology of the fungus, it is unlikely that the ability to cause severe necrotic damage on stems and branches is important for the fungus because the formation of its apothecia takes place on the decaying ash leaves on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fraxineus , local ash species are resistant to the fungus although it is a foliar pathogen (Cleary et al , ; Drenkhan et al , ). Nielsen et al () further showed that the pathogen could grow and reproduce on leaf rachises of different ash species that were not affected by ash dieback. Based on the accumulating knowledge on the ecology of the fungus, it is unlikely that the ability to cause severe necrotic damage on stems and branches is important for the fungus because the formation of its apothecia takes place on the decaying ash leaves on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…The seedlings were grown in pots under disease‐free conditions in a greenhouse for 2 years and were free of visible infection at the time of inoculation. The seedlings were inoculated by inserting infected wood plugs of ash into a small incision in the bark of the seedlings, as described in Nielsen et al (). The wood plugs had been infected by placing on Petri dishes with the single‐spore H .…”
Section: Methodsmentioning
confidence: 99%
“…Although most plant species are susceptible to infection and damage by one or more pathogens, some species or individuals may exhibit different degrees of susceptibility [50]. For example, within the genus Fraxinus, there is large variation between species in susceptibility to the ash dieback pathogen Hymenoscyphus fraxineus [51,52] (see Section 3.1 Case studies), and large genotypic effects in susceptibility among individuals of European ash (Fraxinus excelsior L.) [53]. Similarly, R. lauricola affects several members of the laurel family (Lauraceae) in the USA though lethal damage is most prominent on only a few native hosts including red bay (Persea borbonia (L.) Spreng.…”
Section: Diversitymentioning
confidence: 99%
“…pennsylvanica are susceptible to ADF 14 and observations from Russia show that F. excelsior are infested by EAB 22 , there seem to be variation among species. Establishing experimental plots is a necessary action step.…”
Section: Rapid Resistance Breeding Coupled With Phenotype-based Methodsmentioning
confidence: 95%